Neuropatia periférica em pessoas com mieloma múltiplo - Maysa Mayran Chaves Moreira (2018)
Objective: To investigate the prevalence and incidence of peripheral neuropathy (PN) related to antineoplastic therapy in people with multiple myeloma and the association between chemotherapy regimens and peripheral neuropathy after treatment. Method: This is a documentary and correlational study carried out in two reference sites for cancer treatment, located in the Brazilian states of Ceará and Minas Gerais, with an analysis of patients treated between January 2013 and January 2016. A descriptive and inferential analysis of data was carried out by means of chi-square and Fischer’s exact tests. Results: The study assessed 100 medical records of people with multiple myeloma, who were aged 62.7 years on average and were mostly men (64%). The most used chemotherapy regimen (60%) was bortezomib, dexamethasone, and cyclophosphamide; 20% of patients had peripheral neuropathy before treatment, 68% had it during treatment and 56% at the end of treatment. There was no association between chemotherapy regimens and peripheral neuropathy after treatment.Conclusion: Our study showed an increase in the incidence of PN in individuals undergoing treatment of multiple myeloma, 80% had symptoms of neuropathy before and/or during and/or after treatment with chemotherapy regimens. Predominance was of elderly retired men. The most common chemotherapy regimen was bortezomib/dexamethasone/cyclophosphamide and there was no association between regimens used and PN after treatment. The implications of these observations rest on the need for a permanent assessment of PN in people with multiple myeloma, in addition to a strict follow-up to this event in the course of treatment and after it, as well as the management of adverse events and alterations related to the disease. There was no association between chemotherapy regimens and peripheral neuropathy after treatment. It is expected that the results obtained help in the organization of a data record about PN in patients with cancer, with the main purpose of establishing targets of intervention, thus making care more effi cient and comprehensive.